A Study of the Natural Regeneration of Phoenician Juniper (Juniperus phoenicea L.) in the Sidi Khaled Area, West of Derna, Libya (Comprehensive Journal of Science, 2026)
This study aimed to evaluate the natural regeneration potential of Phoenician juniper ( Juniperus phoenicea ) and to assess the influence of environmental conditions and and human activities on its reproduction and growth in the Sidi Khaled area , west of Derna city . Two sites where the species occurs in relatively good condition were selected , and each covering 500 m2 . All trees and seedlings were inventoried , and canopy cover of J. phoenicea as well as associated vegetation was measured . Seedling abundance was monitored over four annual surveys .At Site 1 , seedling numbers declined progressively after the first survey , which recorded 13 seedlings in plot A and 8 in plot B . At Site 2 , initial seedling numbers were lower ( 7 in plot A and 6 in plot B ) , and complete seedling disappearance was observed by the third and fourth surveys . Site 2 exhibited lower vegetation density and greater disturbance due to its proximity to residential areas . Overall , the results indicate that drought exerts a stronger negative effect on Phoenician juniper regeneration than livestock grazing . Although adult trees appear healthy , limitations in natural growth reduce their ability to regenerate and sustain population continuity over time .
Keywords: Juniperus pheonicea , Natural regeneration , Crown coverage , seedling , Drouht